Integrasi Pelajaran Pendidikan Agama Islam Dan Sains Di Ma Syafa’aturrosul Teluk Kuantan - Ikrima Mailani; Munzir Hitami; Abu Anwar (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2022)
The integration of Islamic education in science learning is a very important thing to do,given that if humans are smart without religion they will be like walking robots, willnot be sensitive to others and the social environment, therefore the internalization ofIslamic knowledge into learning and science is absolutely necessary. Thus, in thedevelopment of many models put forward by several education experts, one of whichis the integration of science and religion in the learning process. Islamic religiouseducation learning must be able to translate something that is still felt into meaningand value and must be lived by students. Science and religion from an Islamic point ofview, which have the same metaphysical basis and aim to express and pursueknowledge. It is hoped that the integration of Islamic religious education, science andtechnology will make the learning achieved more meaningful and understandable.Therefore, the purpose of Islamic religious education is to know, understand,appreciate, believe, believe and be sublime in practicing Islamic teachings from the main source: the holy book of the Qur'an and Al Hadith. Through educationalactivities it is possible to practice and use experience.